Reversible Lysine Modification on Proteins by Using Functionalized Boronic Acids. Issue 22 (20th April 2015) - Cal, Pedro M. S. D.; Frade, Raquel F. M.; Cordeiro, Carlos; Gois, Pedro M. P.
Abstract Iminoboronates have been utilized to successfully install azide and alkyne bioorthogonal functions on proteins, which may then be further reacted with their bioorthogonal counterparts. These constructs were also used to add polyethylene glycol (PEG) to insulin, a modification which has been shown to be reversible in the presence of fructose. Finally, iminoboronates were used to assemble a folic acid/paclitaxel small‐molecule/drug conjugate in situ with an IC50 value of 20.7 nM against NCI‐H460 cancer cells and negligible cytotoxicity against the CRL‐1502 noncancer cells.